A new design approach for dual‐band patch antenna serving Ku/K band satellite communications. (3rd August 2015) - Ahsan, M. R.; Islam, M. T.; Habib Ullah, M.; Aldhaheri, R. W.; Sheikh, M. M.
Summary: A printed planar antenna with simple and intelligent geometrical structure has been proposed for Ku/K band satellite communication systems. The radiating patch of the antenna is formed by cutting rectangular slots and extending the radiating element to some extent. The final design of the antenna with optimized parameters is fabricated on ceramic–polytetrafluoroethylene substrate materials of dielectric constant εr = 10.2. The antenna is excited through a microstrip feed line and has reduced ground plane that covers only the non‐radiating portion of the antenna. The reduced complexity of the antenna is easy to fabricate and has overall dimension of 40 × 35 × 1.905 mm 3 . The results from experimental analysis show that the proposed antenna can guarantee a wide bandwidth of 12.0 to 16.4 GHz at lower band, and the upper band covers the frequency in the range of 17.53 to 19.5 GHz. The antenna has achieved appreciable gain in the range of 3.14 to 4.68 dBi for lower band and 2.03 to 3.65 dBi for upper band. The proposed antenna has offered almost symmetrical and directional radiation pattern that is essentially suitable for serving Ku/K band satellite applications. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A modified rectangular slotted patch antenna of 40 × 35 × 1.905 mm 3 has been proposed and fabricated on ceramic‐polytetrafluoroethylene substrate of dielectric constant ε r = 10.2. The results from experimental analysis show that the antenna covers 12.0 to 16.4 GHz for Ku band and 17.53 to 19.5 GHz for K band satellite and radar applications. The proposed antenna has achieved good reflection coefficients over the operating bands and satisfactory gain characteristics; this antenna is reasonably suitable candidate for Ku/K band satellite applications.